Logika Spiritual dan Model Resistensi Keagamaan dalam Serat Darmasonya - Arif Hartarta; Aris Aryanto (Jurnal Lektur Keagamaan, 2016)
It has been said that spirituality is the fire at the heart of religious teaching – that spirituality is the true destination of a religious life. This article examines a single manuscript entitled “Serat Darmasonya” (here-in¬after abbreviated as SD), a manuscript that describes the know¬ledge of the Shari'a in the congregation. This literature gives critical commentary of the activity of various traditions, particularly in Java. In this study the authors focused on two aspects, namely: 1) the spiritual logic of the SD text, and 2) an example of religious resistance to the elements of tradition. This study is a form of qualitative research concentrating on the analysis of the text. Reading of the text is conducted using the heuristic and hermeuneutic methods. By the end of the Majapahit era there emerged a Dar masunya manuscript which later became the book of guidance addressed to the adherents of Siwa-Buddha. Later, in the early 20th century appeared other books of the same title with Islamic nuances. Darmasonya text explains some advice about the attitude of Muslims according to the Qur’an and the Hadith, and the books of religious doctrines from an earlier period. The Darmasonya text also gives a variety of criticisms regarding the attitude of life, which is a series of patterns, discipline, laws or rules derived from the supreme ruler of the universe. The teaching in the text is somewhat abstract, but it was highly valued by the authors, and by some other groups as a one of main moral points of reference in Java. Keywords: Fiber Darmasonya, Java Manuscript, Islam, Spiritual Logics, Tradition, Resistance. Sering dikatakan bahwa spiritualitas adalah api dari ajaran agama, di mana spiritualitas dianggap sebagai jalan sekaligus tujuan kehidupan keagamaan. Artikel ini mengkaji naskah tunggal berjudul Serat Darma¬sonya (yang selanjutnya disingkat SD) yaitu sebuah pustaka yang menjelaskan pengetahuan tentang ilmu syariat dan tarekat. Pustaka ini mengajukan tafsir-tafsir kritis terhadap aktivitas berbagai tradisi, khususnya di Jawa. Dalam kajian ini penulis menitikberatkan pada dua hal, yaitu: 1) logika spiritual dalam teks SD, dan 2) model resistensi keagamaan terhadap unsur tradisi. Bentuk kajian ini adalah penelitian kualitatif yang berkonsentrasi pada analisis teks. Pembacaan terhadap teks dilakukan dengan dua cara: heuristik dan hermeuneutik. Pada masa Majapahit akhir telah muncul lontar Darmasunya yang kemudian menjadi kitab panduan penganut ajaran Siwa-Buddha. Belakangan, pada sekitar awal abad 20 (muncul kitab lain yang bernuansa Islami dengan judul sama. Teks Darmasonya memaparkan petuah tentang sikap hidup seorang Muslim berdasarkan Al Quran, Hadits, dan kitab-kitab spiritual keagamaan terdahulu. Teks Darmasonya juga menyuguhkan beragam kritik mengenai sikap hidup, yakni sederetan pola abstrak, disiplin, hukum-hukum atau aturan yang berasal dari penguasa tertinggi jagad raya. Ajaran dalam teks tersebut merupakan sesuatu yang abstrak namun dipandang berharga oleh pengarang atau kelompok tertentu serta dijadikan acuan moralitas dalam menjalani arah kehidupan di Jawa. Keywords: Serat Darmasonya, Naskah Jawa, Islam, Logika Spiritual, Resistensi, Tradisi.